2011
DOI: 10.1002/ange.201103563
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular and Selective Synthesis of 2,4,5‐Trisubstituted Oxazoles by a Gold‐Catalyzed Formal [3+2] Cycloaddition

Abstract: Scheme 4. Scope for the gold-catalyzed oxazole cycloaddition. [a] [a] Reaction conditions: 1(b-g) (1.5 equiv), 2(a-l) (1.0 equiv) and [Au-I] (5 mol %) in toluene (0.1 m) were reacted at 90 8C. Reactions were monitored by TLC and stopped after the time shown in parentheses. Yields refer to isolated product after column chromatography. [b] Contaminated with < 5 % of the 5-vinyloxazole from HBr elimination. TBDPS = tert-butyldiphenylsilyl. Angewandte Chemie 9095

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(22 citation statements)
references
References 95 publications
1
20
0
1
Order By: Relevance
“…Davies 48 reported that 2,4,5-trisubstituted oxazoles 211 could be synthesized from ynamides 210 and 1,3- N , O- dipole equivalents 209 in a gold (III) catalyzed process (Scheme 40). …”
Section: Cycloadditions and Formal Cycloadditionsmentioning
confidence: 99%
“…Davies 48 reported that 2,4,5-trisubstituted oxazoles 211 could be synthesized from ynamides 210 and 1,3- N , O- dipole equivalents 209 in a gold (III) catalyzed process (Scheme 40). …”
Section: Cycloadditions and Formal Cycloadditionsmentioning
confidence: 99%
“…[10] Due to the p-acid and electron-donor dual reactivity of gold catalysts, alkynes can be used as precursor of a gold carbenoid, albeit with several exceptions. [11] Leaving group-bearing nucleophiles such as sulfoxide, [12] pyridine/quinoline N-oxide, [13] nitrone, [14] nitro, [15] azide, [16] pyridine N-aminide, [17] sulfur ylide, [18] epoxide [19] and iminopyridium ylide [20] can be used to obtain a carbene intermediate. Many unconventional and efficient transformations to access molecules which are not easily available through traditional organic reactions have been realized.…”
mentioning
confidence: 99%
“…Other new reactions with alkynes have also been described by combining iminopyridinium ylides with gold catalysts, which leads to the production of either amidines or oxazoles. [52] However, as fairly concluded by the Davies group, these reactions rather involve nitrene equivalents. Addition of the ylides onto gold-activated alkynes followed by elimination of the neutral pyridine ring leads to a-imino gold carbene intermediates that are otherwise difficult to prepare by application of classical gold carbene chemistry.…”
Section: Reactions With Alkynesmentioning
confidence: 91%